Model of Destination Attributes and Culture in Increasing Revisit Intention Through Memorable Tourism Experience on Temple Tourism in Karawang - Sekar Ayu Puspitasari; Citra Savitri; Syifa Pramudita Faddila (International Journal of Economics and Management Research, 2025)
The Covid-19 pandemic has placed the tourism sector among the most impacted, putting Indonesia under considerable pressure. Temples have great potential as a culturally focused tourist destination that provides unique and unforgettable experiences, but their management needs to be improved. The purpose of this study was to study how destination attributes and cultural elements influence the desire to revisit through memorable tourism experiences. The method used is a verifiable quantitative method. This study utilizes a sample of 100 respondents who have visited the temple in Karawang at least 1 time. Sampling was carried out using a non-probability sampling technique , namely the Structural Equation Modeling (SEM) method. The results showed that destination and cultural attributes significantly influenced memorable tourism experiences and revisit intentions. A memorable tourism experience proves to be an important mediator in the relationship between destination attributes and culture and revisit intention. The activity factor in destination attributes and authenticity in culture play an important role in creating a memorable experience. This study recommends increasing activity-based tourism attraction and cultural preservation to support tourism sustainability in Karawang.